The Requirement of the C-Terminal Domain of GluA1 in Different Forms of Long-Term Potentiation in the Hippocampus Is Age-Dependent - Liu, An; Ji, Hong; Ren, Qiaoyun; Meng, Yanghong; Zhang, Haiwang; Collingride, Graham; Xie, Wei; Jia, Zhengping (Frontiers in Synaptic Neuroscience, 2020)
Long-term potentiation (LTP) at glutamatergic synapses is an extensively studied form of long-lasting synaptic plasticity widely regarded as the cellular basis for learning and memory. At the CA1 synapse, there are multiple forms of LTP with distinct properties. Although AMPA gluta-mate receptors (AMPARs) are a key target of LTP expression, whether they are required in all forms of LTP remains unclear. To address this question, we have used our recently developed mouse line, GluA1C2KI, where the c-terminal domain (CTD) of the endogenous GluA1 is replaced by that of GluA2. Unlike traditional GluA1 global or conditional KO mice, GluA1C2KI mice have no changes in basal AMPAR properties or synaptic transmission allowing a better assessment of GluA1 in synaptic plasticity. We previously showed that these mice are impaired in LTP induced by high frequency stimulation (HFS-LTP), but whether other forms of LTP are also affected in these mice is unknown. In this study, we compared various forms of LTP at CA1 synapses be-tween GluA1C2KI and wild-type littermates by using several induction protocols. We show that HFS-LTP is impaired in both juvenile and adult GluA1C2KI mice. The LTP induced by theta-burst stimulation (TBS-LTP) is also abolished in juvenile GluA1C2KI mice. Interestingly, TBS-LTP can still be induced in adult GluA1C2KI mice, but its mechanisms are altered becoming more sensitive to protein synthesis and the extracellular signal-regulated kinase (ERK) inhibitors compared to wild type control. The GluA1C2KI mice are also differentially altered in several forms of LTP in-duced under whole-cell recording paradigms. These results indicate that the CTD of GluA1 is dif-ferentially involved in different forms of LTP at CA1 synapse highlighting the complexity and adaptative potential of LTP expression mechanisms in the hippocampus.